Do motor control genes contribute to interindividual variability in decreased movement in patients with pain? - Mishra Bikash K; Wu Tianxia; Belfer Inna; Hodgkinson Colin A; Cohen Leonardo G; Kiselycznyk Carly; Kingman Albert; Keller Robert B; Yuan Qiaoping; Goldman David; Atlas Steven J; Max Mitchell B (SAGE Publishing, 2007)
Abstract Background Because excessive reduction in activities after back injury may impair recovery, it is important to understand and address the factors contributing to the variability in motor responses to pain. The current dominant theory is the "fear-avoidance model", in which the some patients' heightened fears of further injury cause them to avoid movement. We propose that in addition to psychological factors, neurochemical variants in the circuits controlling movement and their modification by pain may contribute to this variability. A systematic search of the motor research literature and genetic databases yielded a prioritized list of polymorphic motor control candidate genes. We demonstrate an analytic method that we applied to 14 of these genes in 290 patients with acute sciatica, whose reduction in movement was estimated by items from the Roland-Morris Disability Questionnaire. Results We genotyped a total of 121 single nucleotide polymorphisms (SNPs) in 14 of these genes, which code for the dopamine D2 receptor, GTP cyclohydrolase I, glycine receptor α1 subunit, GABA-A receptor α2 subunit, GABA-A receptor β1 subunit, α-adrenergic 1C, 2A, and 2C receptors, serotonin 1A and 2A receptors, cannabinoid CB-1 receptor, M1 muscarinic receptor, and the tyrosine hydroxylase, and tachykinin precursor-1 molecules. No SNP showed a significant association with the movement score after a Bonferroni correction for the 14 genes tested. Haplotype analysis of one of the blocks in the GABA-A receptor β1 subunit showed that a haplotype of 11% frequency was associated with less limitation of movement at a nominal significance level value (p = 0.0025) almost strong enough to correct for testing 22 haplotype blocks. Conclusion If confirmed, the current results may suggest that a common haplotype in the GABA-A β1 subunit acts like an "endogenous muscle relaxant" in an individual with subacute sciatica. Similar methods might be applied a larger set of genes in animal models and human laboratory and clinical studies to understand the causes and prevention of pain-related reduction in movement.